Analisis 7 Atribut e-Commerce Berbasis Website sebagai Dasar Preferensi Konsumen di Kota Bandung dengan Pendekatan Analisis Konjoin - Suciati Puspitaningrum; Cut Irna Setiawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2021)
Abstract The lifestyle in the era resulted in people's behavior, one of the activities and related to modern technology is e-commerce. This study aims to define the consumer preferences in Bandung when choosing e-commerce. Respondents in this study were 100 people who live in Bandung and who have used e-commerce, especially Shopee, Tokopedia, Bukalapak, Lazada, Blibli. The sampling method is a non-probability sampling technique. The method used in this research is a quantitative type using technical descriptive analysis and conjoint analysis. With 18 stimuli questions using a Likert scale. The results showed that there was a utility value at the attribute level of cash on delivery by the score is 0.208, an important attribute was in the payment method by the score is 23,882, and the highest consumer value index was stimulation with the combination of attribute payment method (cash on delivery), shipping costs (fixed) cost delivery, delivery speed (order now and sent now), the product warranty (can be exchanged for the same product), security (the website uses a data security system), product (product according to the description provided), website display (product advertisements on website view).